Zambia : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Waiver of Nonobservance of Performance Criteria and Modification of Performance Criteria, and Financing Assurances Review. (IMF Staff Country Reports; Country Report, 2010)
Zambia's strong performance continues under the Extended Credit Facility-supported program. All but one of the quantitative performance criteria were met, and structural reforms are progressing. In the aftermath of exchange rate and copper price fluctuations, the financial sector's recovery has been slow. The main macroeconomic policy challenge in future is to increase growth further by creating fiscal space for expenditures that would enhance economic diversification and reduce Zambia's dependence on copper exports. Monetary policy appropriately targets a further reduction in underlying inflation.